Regulatory reforms in selected EU network industries - Reiner Martin; Moreno Roma; Isabel Vansteenkiste (European Central Bank (ECB), 2005)
In the course of the 1990s, the EU has embarked on an ambitious regulatory reform programme for a number of European network industries, such as telecommunications, energy and transport. This paper analyses the potential benefits of successful reforms in these sectors with a focus on the price effects of regulatory reforms. Following a review of the existing empirical literature in this field, the paper discusses the evolution of the current regulatory framework for network industries in the EU. An empirical analysis of the main determinants of recent price developments in these industries provides evidence that regulatory reform measures had a substantial downward impact on prices in the four sectors under review.
Keywords: E30; L33; L51; L93; L94; L95; L96; 330; Network Industries; Panel Data; Price effects; Regulatory Reforms.; Deregulierung; Telekommunikationspolitik; Luftverkehrspolitik; Bahnpolitik; Postrecht; EU-Staaten; EU-Energiepolitik